APLIKASI PENDAFTARAN SISWA BARU DENGAN BOOTSTRAP PHP DAN MYSQL: STUDI KASUS SMK IT BAITUL AZIZ - Risi Siti Fatimah; Fadzar Rusghana (Melati Institute, 2023)
The development of technology and science is very rapid, especially in the field of computers which makes computer devices equipped with application programs so that they can be utilized to the fullest. Along with the development of technology in this globalization era, it can make it easier for people to carry out learning, education and other activities because the existence of a website-based application program can accelerate information conveyed quickly and precisely. The registration of new students has a close relationship with educational activities, starting from filling in the prospective student data form, filling in the parent data form, and filling in the data for prospective new students which takes quite a long time. This final project uses the waterfall (Performance, Information, Economic, Control, Efficiency, and Service) method and to describe the running system the author uses UML (Unified Modeling Language). This system was created in order to simplify the registration process and the process of making new student registration reports.